The Influence of Organizational Climate and Competence on Commitment and Performance of Rectorate Employees: Riau University, Pekanbaru - Falkoni Falkoni; Susi Hendriani; Syapsan Syapsan (Bahtera Inovasi, 2023)
This study aims to determine and analyze the effect of organizational climate and competence on organizational commitment. To find out and analyze the influence of organizational climate and competence on employee performance. To determine and analyze the effect of organizational commitment on employee performance and To determine and analyze the effect of organizational climate and competence on performance through organizational commitment. In this study, the population is non-educational employees as many as 125 civil servants and Honorer employees. While the sample used as many as 25 people. The data used in this study were primary data and secondary data, while the data collection technique used a questionnaire. The data analysis technique used in this study is the data analysis used in this study is SEM. Organizational climate affects commitment. Competence affects commitment. Organizational climate has an effect on employee performance. Competence affects the performance of employees. Commitment has a significant effect on employee performance. Organizational climate has a significant effect on employee performance through commitment. AndCompetence has a significant effect on employee performance through commitment.